Preferences for Depression Treatment Including Internet-Based Interventions: Results From a Large Sample of Primary Care Patients - Dorow, Marie; Löbner, Margrit; Pabst, Alexander; Stein, Janine; Riedel-Heller, Steffi G. (Frontiers in Psychiatry, 2018)
Background: To date, little is known about treatment preferences for depression concerning new media. This study aims to (1) investigate treatment preferences for depression including internet-based interventions and (2) examine subgroup differences concerning age, gender and severity of depression as well as patient-related factors associated with treatment preferences. Methods: Data were derived from the baseline assessment of the @ktiv-trial. Depression treatment preferences were assessed from n=641 primary care patients with mild to moderate depression regarding the following treatments: medication, psychotherapy, combined treatment, alternative treatment, talking to friends and family, exercise, self-help literature, and internet-based interventions. Depression severity was specified by GPs according to ICD-10 criteria. Ordinal logistic regression models were conducted to identify associated factors of treatment preferences. Results: Patients had a mean age of 43.9 years (SD = 13.8) and more than two thirds (68.6%) were female. About 43% of patients had mild depression while 57% were diagnosed with moderate depression. The majority of patients reported strong preferences for psychotherapy, talking to friends and family, and exercise. About one in five patients was very likely to consider internet-based interventions in case of depression. Younger patients expressed significantly stronger treatment preferences for psychotherapy and internet-based interventions than older patients. The most salient factors associated with treatment preferences were the patients’ education and perceived self-efficacy. Conclusions: Patients with depression report individually different treatment preferences. Our results underline the importance of shared decision-making within primary care. Future studies should investigate treatment preferences for different types of internet-based interventions.